2009
DOI: 10.1002/mnfr.200800575
|View full text |Cite
|
Sign up to set email alerts
|

Influence of apple polyphenols on inflammatory gene expression

Abstract: Apples (Malus spp., Rosaceae) and products thereof contain high amounts of polyphenols which show diverse biological activities and may contribute to beneficial health effects, like protecting the intestine against inflammation initiated by chronic inflammatory bowel diseases (IBD). IBD are characterized by an excessive release of several proinflammatory cytokines and chemokines by different cell types which results consequently in an increased inflammatory response. In the present study we investigated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
103
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 82 publications
(65 reference statements)
8
103
1
3
Order By: Relevance
“…According to data in the literature apples contain more phenols (Jung et al, 2009) and mandarins more vitamin C and specific flavonoids and carotenoids (Sentandreu et al, 2007). This finding is in accordance with that of previous studies in which animals supplemented with different fruits shown different responses in the parameters of oxidative stress (Pajk et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…According to data in the literature apples contain more phenols (Jung et al, 2009) and mandarins more vitamin C and specific flavonoids and carotenoids (Sentandreu et al, 2007). This finding is in accordance with that of previous studies in which animals supplemented with different fruits shown different responses in the parameters of oxidative stress (Pajk et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Values not sharing the same letter were significantly different (p \ 0.05, Fisher's test) PGE 2 , and TNF-a, with oligomers poorly effective with respect to polymers that contributed almost entirely to the HPE activity. These data may be the reflection of the amounts of proanthocyanidins assayed and/or indicate a different ability of oligomers and polymers to affect the macrophage response, as observed in other researches [44,[46][47][48][49]. To further highlight the role of these components, PF was also found almost effective as the whole HPE in inhibiting phosphorylation, and then activation, of IjB-a.…”
Section: Discussionsupporting
confidence: 54%
“…Transient transfections of MonoMac6 cells were performed by electroporation (Bio-Rad, Munich, Germany, Gen Pulser) 3Â10 7 cells ml À1 in 0.4 ml RPMI 1640 medium Ganodermycin, a novel inhibitor of CXCL10 expression M Jung et al containing 25 mM HEPES buffer together with 40 mg of the indicated plasmids at 200 V and 975 mF. 19 After electroporation the cells were seeded at 1Â10 6 cells ml À1 RPMI 1640 medium containing 10% fetal calf serum in a 24-well plate with and without test compounds, and luciferase expression was induced with 1 mg ml À1 LPS and 10 ng ml À1 IFN-g. Luciferase activity was measured 4 h after induction using the luciferase assay system (Promega) according to the manufacturer's instructions with a luminometer. For analyzing CXCL10 synthesis, MonoMac6 cells were starved for 16 h in RPMI 1640 medium containing 0.5% fetal calf serum, pretreated for 1 h with the test compound and subsequently induced with 1 mg ml À1 LPS and 10 ng ml À1 IFN-g for additional 16 h. Subsequently, the cells were centrifuged and the cell culture supernatant was analyzed using the CXCL10 ELISA kit (R&D Systems, Wiesbaden-Nordenstadt, Germany) according to the manufacturer's instructions.…”
Section: Biological Assaysmentioning
confidence: 99%